2016
DOI: 10.1016/j.wneu.2016.09.063
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Characterization of a Multifocal Ganglioglioma Originating Within the Spinal Cord

Abstract: BACKGROUND Gangliogliomas are rare, low-grade intra-axial tumors that exhibit both neuronal and glial components. Although the vast majority present as an intracranial lesion, a rare subset exist as isolated lesions of the spinal cord. Gangliogliomas have also been shown to harbor mutations in the p53 tumor suppressor gene and BRAF oncogene. Previous studies in ganglioglioma have correlated p53 mutations with histologic transformation and BRAF mutations with worse prognosis. CASE DESCRIPTION In this report, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 22 publications
0
2
0
Order By: Relevance
“…One study by Gessi et al 22 found that spinal gangliogliomas do not harbor the BRAF V600E mutation in high frequency. Another study by Wang et al 23 acknowledged that very little work has been done in regards to understanding the role of BRAF mutations in spinal cord tumors. Ryall et al 18 reported the presence of both BRAFV660E , FGFR1 single nucleotide variants, as well as KIAA1549–BRAF and FGFR1–TACC1 fusions in spinal cord LGG.…”
Section: Discussionmentioning
confidence: 99%
“…One study by Gessi et al 22 found that spinal gangliogliomas do not harbor the BRAF V600E mutation in high frequency. Another study by Wang et al 23 acknowledged that very little work has been done in regards to understanding the role of BRAF mutations in spinal cord tumors. Ryall et al 18 reported the presence of both BRAFV660E , FGFR1 single nucleotide variants, as well as KIAA1549–BRAF and FGFR1–TACC1 fusions in spinal cord LGG.…”
Section: Discussionmentioning
confidence: 99%
“…[4,8] However, one case of lowgrade GG has been reported to harbor TP53 mutation. [27] e NF1 mutations found in this tumor were believed to cause premature truncation and loss of function of the NF1 protein based on their location. NF1 loss of function has been observed in many tumor types and results in elevated levels of active GTP-bound RAS and activation of MAP-Kinase and PI3K pathways.…”
Section: Tumor Molecular Profilementioning
confidence: 99%